Hepatocellular carcinoma occurrence does not differ between interferon‐based and interferon‐free treatment with liver histological assessment. Issue 3 (8th January 2020) - Tahata, Yuki; Sakamori, Ryotaro; Urabe, Ayako; Yamada, Ryoko; Ohkawa, Kazuyoshi; Hiramatsu, Naoki; Hagiwara, Hideki; Oshita, Masahide; Hijioka, Taizo; Tamura, Shinji; Imai, Yasuharu; Kodama, Takahiro; et al.
Abstract : Aim: Several studies have recently reported that hepatocellular carcinoma (HCC) occurrence does not differ between hepatitis C virus patients receiving interferon (IFN)‐based and IFN‐free treatments considering the patients' backgrounds. However, liver fibrosis was not directly considered in these studies. Methods: In total, 3972 patients without a history of HCC who started IFN‐based or IFN‐free treatment between August 2002 and April 2017 at 30 Japanese hospitals and achieved a sustained virologic response were included. Propensity score matching considering liver histology was performed. Results: The median age and percentage of patients with advanced liver fibrosis (F3/4) were 58 years and 11.4% in the IFN‐based group, and 68 years and 18.9% in the IFN‐free group, respectively. The HCC occurrence rates at 1 year and 2 years were 0.4% and 1.1% in the IFN‐based group, and 1.6% and 4.1% in the IFN‐free group, respectively, and HCC occurrence in the IFN‐free group was significantly higher than that in the IFN‐based group ( P < 0.001). The characteristics of the HCC occurrence patterns did not differ between the two groups. After propensity score matching, among 764 patients, the HCC occurrence rates at 1 year and 2 years were 0.5% and 1.9% in the IFN‐based group and 1.1% and 3.0% in the IFN‐free group, respectively, and no significant difference was observed between the two groups ( P = 0.489). Conclusions: HCC occurrence in sustained virologic response patients does not differ between IFN‐based and IFN‐free treatment considering liver fibrosis stage. The degree of its progress at diagnosis does not differ between the two groups.